Y = 2 3 ⋅ 6 2 ⋅ f ( 3 ) f ′ ′ ( α ) f ′ ′ ( β ) f ′ ′ ( γ ) f ′ ′ ( δ )
Let the zeros of the function
f
(
x
)
=
x
4
−
3
x
3
−
6
x
2
+
9
x
+
6
be
α
,
β
,
γ
,
δ
.
Evaluate the expression above.
Clarification : f ′ ′ ( x ) denotes the second derivative of f ( x ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
are you preparing for jee ?
Log in to reply
No.. I have already given JEE and destroyed it..... :-(
Log in to reply
you mean you cleared it with great rank or failed ?
Log in to reply
@A Former Brilliant Member – Destroyed means screwed my paper. ... Obviously I didn't failed it but my rank was not good.
f ( x ) = x 4 − 3 x 3 − 6 x 2 + 9 x + 6 = ∏ ( x − α ) = ∏ ( α − x ) (1)
f ′ ′ ( x ) = 1 2 x 2 − 1 8 x − 1 2 = 1 2 ( x + 2 1 ) ( x − 2 )
∏ f ′ ′ ( α ) = ∏ 1 2 ( α + 2 1 ) ( x − 2 ) = 1 2 4 ( ∏ ( α + 2 1 ) ) ( ∏ ( α − 2 ) )
⋯ = 1 2 4 f ( − 2 1 ) f ( 2 ) = 1 2 4 ( 1 6 7 ) ( − 8 ) = − 7 2 5 7 6 Using the result for f(x) from (1)
Y = 2 3 ⋅ 6 2 ⋅ f ( 3 ) ( ∏ f ′ ′ ( α ) ) = 2 8 8 × ( − 2 1 ) − 7 2 5 7 6 = 1 2
Good approach to calculating these values.
Problem Loading...
Note Loading...
Set Loading...
First note since α is a root of f ( x ) ,
α 4 − 3 α 3 − 6 α 2 + 9 α + 6 = 0
⟹ α 4 − 3 α 3 = 6 α 2 − 9 α − 6 . . . ( 1 )
Now double differentiate f ( x ) and put x = α so that f ′ ′ ( α ) = 1 2 α 2 − 1 8 α − 1 2 = 2 ( 6 α 2 − 9 α − 6 ) . Now using ( 1 ) , f ′ ′ ( α ) = 2 ( α 4 − 3 α 3 ) = 2 α 3 ( α − 3 ) .
Hence,
cyc ∏ f ′ ′ ( α ) = cyc ∏ 2 α 3 ( α − 3 ) = 2 4 ( α β γ δ ) 3 cyc ∏ ( α − 3 )
Using Vieta's formula α β γ δ = 6 and put x = 3 in f ( x ) = cyc ∏ ( α − x ) to get cyc ∏ ( α − 3 ) = f ( 3 ) . Hence,
cyc ∏ f ′ ′ ( α ) = 2 4 ⋅ ( 6 ) 3 ⋅ f ( 3 )
⟹ 2 3 ⋅ 6 2 ⋅ f ( 3 ) cyc ∏ f ′ ′ ( α ) = 1 2